The Conjoint Analysis of Microstructural and Morphological Changes of Gray Matter During Aging - Zhao, Xin; Wu, Qiong; Chen, Yuanyuan; Song, Xizi; Ni, Hongyan; Ming, Dong (Frontiers in Neurology, 2019)
Macromorphological and microstructural changes of gray matter (GM) happen during brain normal aging. However, the mechanism of macro-microstructure association is still unclear, which is of guidance for understanding many neurodegenerative diseases. In this study, adopting structural magnetic resonance imaging (sMRI) and diffusion kurtosis imaging (DKI), GM aging pattern was characterized and its macro-microstructure associations were revealed. For 60 subjects between the ages of 47-79, the DKI and T1-weighted images were investigated with voxel-based analysis. The results demonstrated three age-related overlap patterns between morphological and microstructural changes during normal aging. First, morphological changes and MD metric abnormalities obviously overlapped in the following regions, bilateral frontal lobe, temporal lobe, insula and thalamus. Besides, compared to GM atrophies, MD abnormalities were observed in more regions, cingulate gyrus, parietal lobe and occipital lobe. What’s more, in left temporal pole and amygdala, only GM volume changes were detected, and the changes of MD were not found. What important is that intrinsic associations between macrostructure and microstructure were found. Age-independent intrinsic associations revealed the potential mechanisms in the process of aging. The physiological mechanism may be associated with the elimination of neurons and synapses and the shrinkage of large neurons. Understanding the associations of GM volume changes and microstructural changes can account for the underlying mechanisms of aging and age-related neurodegenerative diseases.